Monitoring intra-annual cambial activity based on the periodic collection of twigs - a feasibility study - Luz, Ana Luísa; Pereira, Helena; Lauw, Alexandra; Leal, Sofia (Dendrochronologia, 2014)
This study aims at monitoring the cambial activity and xylogenesis along the growing season under Mediterranean climate using a newly designed sampling method based on the periodic collection of twigs from the crown, in order to test its efficacy. Ten species were selected; seven hardwood (Acer pseudoplatanus L.,Ceratonia siliqua L., Schinus terebinthifolius Raddi, Olea europaea L., Fraxinus angustifolia Vahl, Populus alba L., Quercus suber L.) and three softwood species (Abies alba Mill., Cupressus sempervirens L., Pinus pinea L.). The twigs were collected monthly during one year. After microtome sectioning and staining, the sections were photographed and analyzed to monitor ring development and the period of cambial activity. The twigs revealed large differences in radial growth, within and among species, which might be associated to their particular position in the tree, to the effect of the different crown microclimates, and/or to the crown conformation and type of leaves. The method showed effectiveness in the study of cambial activity, but limitations in the study of ring development due to impossibility of comparing samples. Improvements to the method are proposed, aiming essentially at minimizing the variability among samples.
Keywords: cambial activity; Dendrochronology; growth-ring; Mediterranean; twig sampling

Factors driving growth responses to drought in Mediterranean forests - Pasho, Edmond; Camarero, J Julio; Luis, Martín; Vicente-Serrano, Sergio M (European Journal of Forest Research, 2012)
We lack information regarding the main factors driving growth responses to drought in tree species with different vulnerability against this stressor and considering sites with contrasting climatic conditions. In this paper, we identify the main drivers controlling growth response to a multi-scalar drought index (Standardized Precipitation Index, SPI) in eight tree species (Abies alba, Pinus halepensis, Quercus faginea, Pinus sylvestris, Quercus ilex, Pinus pinea, Pinus nigra, Juniperus thurifera). We sampled forests growing across a pronounced climatic gradient under Mediterranean conditions in north-eastern Spain. To summarize the patterns of growth responses to drought, we used principal component analysis (PCA). To determine the main factors affecting growth responses to drought, correlation and regression analyses were carried out using a set of abiotic (climate, topography, soil type) and biotic (Normalized Difference Vegetation Index, Enhanced Vegetation Index, tree-ring width, diameter at breast height) predictors and the PCs loadings as response variables. The PCA analysis detected two patterns of growth responses to drought corresponding to xeric and mesic sites, respectively. The regression analyses indicated that growth responses to drought in xeric forests were mainly driven by the annual precipitation, while in mesic sites the annual water balance was the most important driver. The management of Mediterranean forests under the forecasted warmer and drier conditions should focus on the main local factors modulating the negative impacts of drought on tree growth in xeric and mesic sites.
Keywords: Dendrochronology; Drought; iberian peninsula; Radial growth; Standardized precipitation index

Impacts of drought at different time scales on forest growth across a wide climatic gradient in north-eastern Spain - Pasho, Edmond; Camarero, J. Julio; de Luis, Martín; Vicente-Serrano, Sergio M. (Agricultural and Forest Meteorology, 2011)
We analyzed the impact of drought measured on different time-scales on radial growth of eight tree species during the period 1950–2005 growing across a wide climatic gradient encompassing semiarid Mediterranean woodlands and wet mountain forests in north-eastern Spain. A drought index (standardized precipitation index, SPI) at different time scales (1–48 months) was correlated with chronologies of ring width to determine the signiﬁcant time scale at which drought affected most tree growth. The ﬁndings indicated that the impact of drought on growth varied noticeably among species and sites. Two distinct patterns were clearly observed considering spatial and temporal differences in the response of species to drought. Species growing in xeric sites (Pinus and Quercus species and Juniperus thurifera) showed the highest responses to SPI time-scales of 9–11 months while those located in mesic sites (Abies alba, Pinus sylvestris) did respond more to SPI time scales shorter than 5 months. The SPI-growth correlations were signiﬁcant, although weak, up to 30 months in xeric sites while no consistent association was observed at higher time scales. Important seasonal differences were noticed in the SPI-growth associations. Species growing in xeric areas responded to spring-summer SPI while those distributed in mesic sites responded more to summer SPI. Our ﬁndings should be useful to understand forest responses to climate change, including an increasing frequency of severe droughts, and to adapt appropriate management strategies to mitigate the impact of drought on tree growth.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Dendrochronology; Drought; Forest growth; Impacts; NE Spain; Standardized precipitation index (SPI)

Vessel features of Quercus ilex L. growing under Mediterranean climate have a better climatic signal than tree-ring width - Campelo, Filipe; Nabais, Cristina; Gutiérrez, Emilia; Freitas, Helena; García-González, Ignacio (Trees, 2010)
We investigated whether vessel time series of Holm oak (Quercus ilex L.), a diffuse to semi-ring-porous species, can record a climatic signal which differs from the signal encoded in tree-ring width (TRW). The study was conducted in ten Q. ilex trees from a coppice stand in northeast Spain. Chronologies of TRW, mean vessel area (MVA) and maximum vessel area (MAX) were developed and correlated with climate data, for the period 1985–2004 (20 years). Our results indicate that vessel features contain environmental information that is different from that stored in TRW. MAX chronologies correlate better to early spring precipitation (April–May) than TRW chronologies, and so does MVA of the largest 20–25 vessels from the ﬁrst third of the ring with late spring precipitation (May–June). Also, the combination of MVA and TRW is a better predictor of summer precipitation. This explorative study clearly shows that vessel features can complement the climatic signal of TRW increasing the resolution of the climate reconstructions for the Mediterranean region.
Keywords: Dendrochronology; Holm oak; Mediterranean climate; Tree ring; Vessel features

Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F; Nabais, C; García-González, I; Cherubini, P; Gutiérrez, E; Freitas, H (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F.; Nabais, C.; García-González, I.; Cherubini, P.; GUTIÉRREZ, E.; Freitas, H. (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163doi: 10.1139/X09-163The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Cork oak (Quercus suber L.) wood growth and vessel characteristics variations in relation to climate and cork harvesting - Leal, Sofia; Nunes, Elsa; Pereira, Helena (European Journal of Forest Research, 2007)
Variations in tree ring growth of Quercus suber L. were analysed using dendrochronological techniques on cork oak discs from trees harvested in the cork producing region of Alentejo, Portugal. A tree-ring chronology containing a strong common signal and covering the period from 1970 to 1995 was build for ca. 30-year-old cork oaks never submitted to cork harvesting using 14 trees that crossdated satisfactorily out of 30 sampled trees. The tree ring indices correlated positively with September temperature (r = 0.48, P < 0.05) and very strongly with precipitation totals from previous October until current February (r = 0.82, P < 0.001) showing that the water stored in the soil during the autumn and winter months prior to the growing season has a primordial effect on the growth of the given season. The effects of cork harvesting were analysed by comparing mean ring width, mean annual vessel area, vessel density (nvessels/mm 2 ), and vessel coverage (percentage of transverse surface occupied by vessels) between three mature cork oak trees and three young trees, for the period from 1987 to 1996, corresponding to the growth between two consecutive cork removals in the case of mature trees. In 1988, 1989 and 1996 (corresponding to the ﬁrst and second years after cork removal, and 1996 to a year of cork removal), the ratios between ring widths of young versus mature trees was twice that for the rest of the period. However, an effect of cork removal indicated by eventual alterations in vessel size and distribution in the wood rings corresponding to the years 1988, 1989 and 1996 in the mature cork oaks was not observed.
Keywords: cork harvesting; Dendrochronology; Precipitation; Quercus Suber L; tree rings; wood anatomy; wood vessels

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Determination of the natural mortality age of an holm oak ( Quercus ilex L.) stand in Corsica (Mediterranean Island) - Panaiotis, C; Carcaillet, C; M'Hamedi, M (Acta Oecologica, 1997)
Determination of old forest stand age and forestry history is problematic due to the difficulties which arise in obtaining core samples from trees. In the present paper, the natural mortality age and forestry history of a Corsican holm oak stand are estimated using the methods described below. Firstly, the correlation between stem age estimated from healthy stump counts in fellings and stem diameter is determined using a second order polynomial equation. Secondly, the distribution of stand diameter classes is analyzed by the BHATTACHARYA (1967) method. This method allows the identifica- tion of cohorts as well as the estimation of cohort mean diameters and theoretical tree count numbers. Using cohort mean diameters, we are able to estimate their age and discuss stand forestry history. Finally, the analysis of thirty broken stumps originating from senescent holm oak natural falls, is used to determine the mean natural mortality age of trees bused on their mean diameter. This natural mor- tality is estimated to occur at 170 -+ 46 years of age. The causes of holm oak mortality and the capacity of old stumps to renew the ecosystem are discussed in order to contribute to the conservation and man- agement of these woodland communities.
Keywords: Corsica; Dendrochronology; Forest structure; mediterranean forest; natural mortality; old forest; Quercus ilex

Thirty years of in situ tree growth under elevated CO2: a model for future forest responses? - Hättenschwiler, S; Miglietta, F; Raschi, A; Körner, C (GLOBAL CHANGE BIOLOGY, 1997)
Rising concentrations of atmospheric carbon dioxide have been predicted to stimulate the growth of forest trees. However, long-term effects on trees growing to maturity and to canopy closure while exposed to elevated CO2 have never been examined. We compared tree ring chronologies of Mediterranean Quercus ilex which have been continuously exposed to elevated CO2 (around 650 mu mol mol(-1)) since they were seedlings, near two separate natural CO2 springs with those from trees at nearby ambient-CO2 `control' sites. Trees grown under high CO2 for 30 years (1964-93) showed a 12% greater final radial stem width than those growing at the ambient-CO2 control sites. However, this stimulation was largely due to responses when trees were young. By the time trees were 25-30 y old the annual difference in tree ring width between low and high CO2 grown trees had disappeared. At any given tree age, elevated CO2 had a relatively greater positive effect on tree ring width in years with a dry spring compared to years with more rainfall between April and May. This indicates a beneficial effect of elevated CO2 on tree water relations under drought stress. Our data suggest that the early regeneration phase of forest stands can be accelerated in CO2-enriched atmospheres and that maximum biomass per land area may be reached sooner than under lower CO2 concentrations. In our study, high CO2 grown Q. ilex trees reached the same stem basal area at the age of 26 y as control trees at 29 y,i.e. three years earlier (faster turnover of carbon?). Reliable predictions of the future development of forests need to account for the variable responses of trees over their entire lifetime. Such responses to elevated CO2 can presently only be assessed at such unique field sites.
Keywords: Basal area; Dendrochronology; forest regeneration; Mediterranean forests; natural CO2 springs; Quercus ilex; Tree ring; water relations

Dating natural gaps in the holm oak forest (Quercus ilex L) in Fango MAB Reserve (Corsica) by reading rings of maquis components - Panaiotis, C; Loisel, R; Paradis, G (Ann. For. Sci., 1995)
This work is related to the study of natural gaps in a Quercus ilex Mediterranean forest in Corsica, France. The aim was to find a way to precisely date the volis to obtain a chronological sample which corresponded to the time of vegetation opening due to the fall of a holm oak and up to complete vegetation closure. The best marker appeared to be Phillyrea latifolia, a typical maquis tree found in association with the holm oak, which has a high capacity to produce stem sprouts after the breakage. In order to date the chablis, rings from the stem sprouts must be counted and a careful observation of the other species must be made to confirm results.
Keywords: Corsica; Dendrochronology; Maquis; natural gap; Quercus ilex